The status of the pledge creditor during the realization of the right of pledge in Macedonian Law - Rodna Zivkovska; Tina Przeska; Tea Lalevska (University in Pristina in Kosovska Mitrovica, Faculty of Law, 2022)
The paper analyses the status and rights of the pledge creditor during the process of realization of the right of pledge. As it is shown in the paper, in Macedonian law one of the main rights of the pledge creditor, in case of default on part of the debtor, is the right to demand realization of the right of pledge by sale of the pledged object, since lex commissoria is granted only in exceptional situations. The analysis of the Macedonian legislation shows that pledge creditors are offered various alternatives to choose from concerning the realization of the right of pledge such as: notary public, enforcement agents, brokers, real-estate agency, although some of the offered alternatives aren’t viable due to insufficient regulation, or due to the fact that they are permitted only when the right of pledge has been acquired by contract (contract pledge). In the legal practice, as the paper will demonstrate, the pledge creditors usually turn to enforcement agents when conditions for realization of the right of pledge are fulfilled. Since enforcement agents act in accordance to the Enforcement Law, the realization of the pledge right is conducted in enforcement proceeding. The core of problems that arise in the enforcement proceedings lays in the fact that the provisions of the Enforcement Law are of general nature, they are not specifically adapted for the purpose of realization of the right of pledge, nor they need to be. As it is shown in the paper, enforcement agents are the ones that need to adapt the conduct of the enforcement proceedings so it would serve the purpose at hand – the realization of the right of pledge. With that in mind, the paper analyses the problems and issues arising in enforcement proceeding and directs to the possible solution based on the nature and regulation of the right of pledge.
Keywords: civil law, property law, right of pledge